Broad-based black economic empowerment ownership deals and their Impact on dividend policy: an empirical study - Pequenino, Derrick Adrian (My University, 2018)
Broad-Based Black Economic Empowerment (BBBEE) has played a significant role in the transformation of the South African economy. One way in which this has been done is through the promotion of ownership by individuals previously disadvantaged under the Apartheid system. These BBBEE ownership promotions schemes are typically highly leveraged and require substantial as well as sustained dividend pay-outs to remain liquid. This may place additional pressure on firms with such BBBEE deals to adopt a more aggressive dividend policy. A panel data regression model was used to test whether firms with BBBEE deals do in fact have higher dividend pay-out ratios, after controlling for the other major determinant of dividend policy (Company Size, Capital Structure, Growth and Investment Opportunities, Liquidity, Profitability and Johannesburg Securities Exchange (JSE) Sector). The panel data regression model was run for JSE listed companies from the year 1999 to 2006. These years of study were selected in order to control for taxation on dividends as this period represented the largest period for which data could be obtained, and for which tax consequences on dividends remained the same. The results for the regression model found that, on average and while controlling for other factors influencing dividend pay-out, the dividend pay-out ratio for companies’ party to a BBBEE deal increased by 7.9% after implementation of the deal. These finding imply that the liquidity of companies may be compromised which could have adverse effects for companies, investors and the overall economy as a whole. Implications for companies include liquidity and bankruptcy concerns as a result of paying out more cash as dividends. Investors, on the other hand, will have to consider whether an increased dividend pay-out ratio is desirable to them, or whether they should seek alternative investments offering higher capital appreciation and less dividend payments. Lastly, the overall economy could suffer from lower growth as a result companies paying higher dividends and keeping less cash on hand to be used for the purpose of fixed asset investment. Keywords: Broad-Based Black Economic Empowerment (BBBEE), Dividend Policy, Dividend Pay out in South Africa, Minorities.
A research report submitted to the Faculty of Commerce, Law and Management, University of the Witwatersrand, Johannesburg, in partial fulfilment of the requirements for the degree of Masters of Commerce (Accountancy), 2018
Keywords: Business enterprises, Black--South Africa; Blacks--South Africa--Economic conditions